Atomic force microscopy for the investigation of molecular and cellular behavior. (October 2016) - Ozkan, Alper D.; Topal, Ahmet E.; Dana, Aykutlu; Guler, Mustafa O.; Tekinay, Ayse B.
Abstract: The present review details the methods used for the measurement of cells and their exudates using atomic force microscopy (AFM) and outlines the general conclusions drawn by the mechanical characterization of biological materials through this method. AFM is a material characterization technique that can be operated in liquid conditions, allowing its use for the investigation of the mechanical properties of biological materials in their native environments. AFM has been used for the mechanical investigation of proteins, nucleic acids, biofilms, secretions, membrane bilayers, tissues and bacterial or eukaryotic cells; however, comparison between studies is difficult due to variances between tip sizes and morphologies, sample fixation and immobilization strategies, conditions of measurement and the mechanical parameters used for the quantification of biomaterial response. Although standard protocols for the AFM investigation of biological materials are limited and minor differences in measurement conditions may create large discrepancies, the method is nonetheless highly effective for comparatively evaluating the mechanical integrity of biomaterials and can be used for the real-time acquisition of elasticity data following the introduction of a chemical or mechanical stimulus. While it is currently of limited diagnostic value, the technique is also useful for basic research in cancer biology and the characterization of disease progression and wound healing processes.